Sleep quality and sleep routines as mediators of stressors and life satisfaction in Czech university students: a structural equation model - Prokeš, Michaela (Frontiers in Psychology, 2023)
Sleep is especially important to overall well-being. Some aspects of sleep have been well documented, for example sleep quantity and its effect on well-being, but the value of a consistent sleep routine remains poorly studied. University students are a population group especially susceptible to stress, mental health problems and poor sleep quality and experience changing daily schedules. Investigating the protective power of sleep in this population group is therefore an important avenue of research.Applying a structural equation model, the current study surveyed a large sample of Czech university students during the covid-19 pandemic in late spring, 2021, and observed the mediation effects of sleep on this group. The study found that working, maintaining social contact and attending lectures in person had a strong effect on satisfaction with life. Increased personal study time indirectly supported consistent sleep routines and mediated perceptions of life satisfaction. As expected, the results indicated the importance of high-quality sleep. The results also verified partial mediation, directly and indirectly, through sleep quality, highlighting the significance of a consistent sleep routine in students on their selfreported satisfaction with life.